Women's education and attitudes toward malaria in children: Evidence from Nigeria - Daniel Tuki (Global Public Health, 2024)
This study examined the effect of women's educational level on their perceptions regarding the deadliness of malaria in children. The regression results revealed that women with primary education did not differ statistically from the reference category (i.e. women with no education) in terms of their likelihood of perceiving malaria as a deadly disease in children. In contrast, women with secondary education were 4.3 percentage points more likely to perceive malaria as a deadly disease compared to the reference category. Similarly, women with higher education were 8 percentage points more likely to perceive malaria as a deadly disease compared to the reference category. These results highlight the crucial role of women's education in shaping their perceptions of disease in children, which also has implications for child health outcomes.
https://doi.org/10.7910/DVN/RKZE7Q
Keywords: I10; I25; I26; J16; 330; Women; attitudes; perceptions; education; malaria; children; Nigeria